Pemanfaatan Website Berbasis Artificial Intelligence Untuk Pengembangan Kompetensi Digital Mahasiswa Jurusan PKK FT UNM: Id - Wardimansyah Ridwan; Israwati Hamsar; Andi Khaerun Niza; Awaluddin; Andi Asti Handayani (Program Studi Sarjana Terapan PTM FT UNM, 2024)
Mastery of Artificial Intelligence (AI)-based technology is one of the important skills for students in the digital era. This community service activity aims to improve the digital competence of students from the Department of Family Welfare Education (PKK), Faculty of Engineering, Makassar State University through training in the use of AI-based websites, such as ChatGPT, Perplexity, Gemini AI, and Grammarly. The training, which was attended by 56 students, lasted for two days, from 20 to 21 September 2024. Activities included an introduction to AI technology, a workshop on using websites, case simulations, and evaluation and reflection. The results of the training showed a significant increase in students' understanding and skills in utilizing AI technology to complete academic assignments, search for information, and manage projects. Participatory, problem-based, and collaborative training methods have proven effective in increasing participant engagement and understanding. This activity is expected to be the first step to integrating AI technology into the learning process and support students' readiness to face the challenges of the digital era.